Teachable moments in the promotion of healthy eating habits, during pregnancy and early childhood - Pearce, Jo (2022)
Nutritional exposures during pregnancy, infancy and early childhood can impact on both the short-term and long-term health outcomes of children. Pregnancy has often been described as a ‘teachable moment’, where women may have increased motivation to change their dietary and other health behaviours. Other teachable moments exist whenever families make choices around nutrition, such as breast or formula feeding, the introduction of solid foods and what to eat at home or at school. This thesis considers whether the promotion of healthy eating habits and adherence to dietary guidelines during these teachable moments, have the potential to improve the health outcomes of women and children.